2019
DOI: 10.1111/2041-210x.13158
|View full text |Cite
|
Sign up to set email alerts
|

Population closure and the bias‐precision trade‐off in spatial capture–recapture

Abstract: 1. Spatial capture-recapture (SCR) is an increasingly popular method for estimating ecological parameters. SCR often relies on data collected over relatively long sampling periods. While longer sampling periods can yield larger sample sizes and thus increase the precision of estimates, they also increase the risk of violating the closure assumption, thereby potentially introducing bias. The sampling period characteristics are therefore likely to play an important role in this bias-precision trade-off.Yet few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…This suggests that the model would estimate a decreased density in the face of mortality. Additionally, researchers have reported that bias in population size estimates should be minimal if the sampling period does not coincide with the peak of the reproductive season (Dupont et al 2019). Because our study sampling began in late May, at the end of the fawning period at the site, we do not think the bias from fawn mortality significantly affected results.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the model would estimate a decreased density in the face of mortality. Additionally, researchers have reported that bias in population size estimates should be minimal if the sampling period does not coincide with the peak of the reproductive season (Dupont et al 2019). Because our study sampling began in late May, at the end of the fawning period at the site, we do not think the bias from fawn mortality significantly affected results.…”
Section: Discussionmentioning
confidence: 98%
“…Older pellets may be from rabbits that are no longer occupying an area, and thus the sample represents what rabbits have been present in the area but are not necessarily present at the time of sampling. This potentially is most important in abundance estimations based on multilocus genotyping where a closed population is assumed (Dupont et al 2019), but because we only recommend the highest quality pellets for genotyping, these are also likely the most recently deposited and representative of the cottontails present. Clearing a transect of pellets a few days prior to sampling would ensure collected pellets are only a few days old, but this necessitates visiting each site twice per collection and could be logistically prohibitive on long transects, such as those favored by intensive monitoring programs.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of density estimated by SCR models is often dependent on the capture-recapture survey duration [ 32 , 93 ]. Most small mammal bioindicators, including Peromyscus , are r -selected species that have high reproductive and mortality rates and generally short lifespans compared with K -selected large mammals [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most small mammal bioindicators, including Peromyscus , are r -selected species that have high reproductive and mortality rates and generally short lifespans compared with K -selected large mammals [ 94 , 95 ]. Therefore, short survey periods should be used for r -selected species to mitigate bias that can result from violating the demographic closure assumption of single-session capture-recapture models [ 32 , 37 ]; however, the potentially optimal survey period length for r -selected species that can produce density estimates with both high precision and accuracy is approximately 14–30 days [ 93 ]. Relative to the life history characteristics of Peromyscus , our five-day survey may have been too short to obtain sufficient data for precisely estimating density-chemical relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation